2013
DOI: 10.3389/fnint.2013.00061
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses at brain barriers and implications for brain development and neurological function in later life

Abstract: For a long time the brain has been considered an immune-privileged site due to a muted inflammatory response and the presence of protective brain barriers. It is now recognized that neuroinflammation may play an important role in almost all neurological disorders and that the brain barriers may be contributing through either normal immune signaling or disruption of their basic physiological mechanisms. The distinction between normal function and dysfunction at the barriers is difficult to dissect, partly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 115 publications
(172 reference statements)
1
61
0
2
Order By: Relevance
“…In addition, within the neuroectoderm, per se, 4) there is a barrier interface between the CSF and the brain interstitial fluid at the apical neuroepithelial membrane (Saunders et al 2008) lined by dense YKL-40 immunoreactivity in the early brain. An important interface in the early steps of the brain barrier development is the blood-CSF barrier (Stolp et al 2013) where we found strong YKL-40 mRNA expression in the choroid plexus. Prominent YKL-40 staining was evident as early as 7 wpc (49 dpc) when the choroid plexus of the lateral ventricles first appears in the human embryonic brain.…”
Section: The Brain Barrier System and Early Angiogenesismentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, within the neuroectoderm, per se, 4) there is a barrier interface between the CSF and the brain interstitial fluid at the apical neuroepithelial membrane (Saunders et al 2008) lined by dense YKL-40 immunoreactivity in the early brain. An important interface in the early steps of the brain barrier development is the blood-CSF barrier (Stolp et al 2013) where we found strong YKL-40 mRNA expression in the choroid plexus. Prominent YKL-40 staining was evident as early as 7 wpc (49 dpc) when the choroid plexus of the lateral ventricles first appears in the human embryonic brain.…”
Section: The Brain Barrier System and Early Angiogenesismentioning
confidence: 75%
“…We showed unique mRNA expression of YKL-40 in the human fetal choroid plexus (Johansen et al 2007), a prominent part of the brain barrier system involved in the process of neuroinflammation (Stolp et al 2013). The distribution of YKL-40 in the developing human forebrain and its possible role in brain barrier sites is unknown.…”
Section: Ykl-40 Neuroinflammation and The Brain Barrier Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Both (a) and (b) extend down the spinal cord; (c) the outer CSF-brain barrier formed by tight junctions between endothelial cells of the arachnoid vessels (pia arachnoid); and (d) the inner CSF-brain barrier formed by strap junctions between the neuro-ependymal cells lining the ventricular surfaces. It is present only in early development and absent in the adult [1]. The above barriers and the blood retinal barrier (not studied here) are parts of a whole realm of barriers.…”
Section: Descriptionmentioning
confidence: 99%
“…It contains four sections; in the first section three papers describe the gates and fences for neuroimmune interactions directly at the central nervous system. Stolp et al (2013) The second section includes two reviews emphasizing the role of hormones on neuro-immune interactions. Quintanar and Guzmán-Soto (2013) describe the role of hypothalamic neurohormones in peripheral immune responses, including the clinical relevance of those hormones.…”
mentioning
confidence: 99%